Effectiveness of en masse versus two-step retraction: a systematic review and meta-analysis - Mumen Z. Rizk; Hisham Mohammed; Omar Ismael; David R. Bearn (SpringerOpen, 2018)
Abstract Background This review aims to compare the effectiveness of en masse and two-step retraction methods during orthodontic space closure regarding anchorage preservation and anterior segment retraction and to assess their effect on the duration of treatment and root resorption. Methods An electronic search for potentially eligible randomized controlled trials and prospective controlled trials was performed in five electronic databases up to July 2017. The process of study selection, data extraction, and quality assessment was performed by two reviewers independently. A narrative review is presented in addition to a quantitative synthesis of the pooled results where possible. The Cochrane risk of bias tool and the Newcastle-Ottawa Scale were used for the methodological quality assessment of the included studies. Results Eight studies were included in the qualitative synthesis in this review. Four studies were included in the quantitative synthesis. En masse/miniscrew combination showed a statistically significant standard mean difference regarding anchorage preservation − 2.55 mm (95% CI − 2.99 to − 2.11) and the amount of upper incisor retraction − 0.38 mm (95% CI − 0.70 to − 0.06) when compared to a two-step/conventional anchorage combination. Qualitative synthesis suggested that en masse retraction requires less time than two-step retraction with no difference in the amount of root resorption. Conclusions Both en masse and two-step retraction methods are effective during the space closure phase. The en masse/miniscrew combination is superior to the two-step/conventional anchorage combination with regard to anchorage preservation and amount of retraction. Limited evidence suggests that anchorage reinforcement with a headgear produces similar results with both retraction methods. Limited evidence also suggests that en masse retraction may require less time and that no significant differences exist in the amount of root resorption between the two methods.